Standardising clinical outcomes measures for adult clinical trials in Fabry disease: A global Delphi consensus - Moreno-Martinez, D; Aguiar, P; Auray-Blais, C; Beck, M; Bichet, D G; Burlina, A; Cole, D; Elliott, P; Feldt-Rasmussen, U; Feriozzi, S; Fletcher, J; Giugliani, R; et al. (Molecular genetics and metabolism, 2021)
BACKGROUND: Recent years have witnessed a considerable increase in clinical trials of new investigational agents for Fabry disease (FD). Several trials investigating different agents are currently in progress; however, lack of standardisation results in challenges to interpretation and comparison. To facilitate the standardisation of investigational programs, we have developed a common framework for future clinical trials in FD. METHODS AND FINDINGS: A broad consensus regarding clinical outcomes and ways to measure them was obtained via the Delphi methodology. 35 FD clinical experts from 4 continents, representing 3389 FD patients, participated in 3 rounds of Delphi procedure. The aim was to reach a consensus regarding clinical trial design, best treatment comparator, clinical outcomes, measurement of those clinical outcomes and inclusion and exclusion criteria. Consensus results of this initiative included: the selection of the adaptative clinical trial as the ideal study design and agalsidase beta as ideal comparator treatment due to its longstanding use in FD. Renal and cardiac outcomes, such as glomerular filtration rate, proteinuria and left ventricular mass index, were prioritised, whereas neurological outcomes including cerebrovascular and white matter lesions were dismissed as a primary or secondary outcome measure. Besides, there was a consensus regarding the importance of patient-related outcomes such as general quality of life, pain, and gastrointestinal symptoms. Also, unity about lysoGb3 and Gb3 tissue deposits as useful surrogate markers of the disease was obtained. The group recognised that cardiac T1 mapping still has potential but requires further development before its widespread introduction in clinical trials. Finally, patients with end-stage renal disease or renal transplant should be excluded unless a particular group for them is created inside the clinical trial. CONCLUSION: This consensus will help to shape the future of clinical trials in FD. We note that the FDA has, coincidentally, recently published draft guidelines on clinical trials in FD and welcome this contribution.
Keywords: klinické zkoušky jako téma; Fabryho nemoc; Glycolipids; trihexosylceramidy; Trihexosylceramides; Consensus; Enzyme Replacement Therapy; Inherited metabolic disorders; konsensus; výsledek terapie; Lysosomal storage disorders; Middle Aged; sfingolipidy; mužské pohlaví; Delphi Technique; alpha-Galactosidase; Adult; Clinical trial; Fabry disease; kvalita života; Fabry Disease; glykolipidy; Clinical Trials as Topic; Isoenzymes; ženské pohlaví; Humans; Globosides; izoenzymy; alfa-galaktosidasa; ledviny; lidé středního věku; globosidy; Sphingolipids; Delphi consensus; delfská metoda; dospělí; Kidney; Female; Quality of Life; enzymová substituční terapie; Clinical outcomes; Treatment Outcome; lidé; Male